Composite strengthening heat treatment method for surface layer of porous sieve-shaped filter

By using 38CrMoAl steel in the porous sieve filter and combining pre-oxidation, ion nitriding and post-oxidation treatments, the problems of temperature uniformity and rust prevention were solved, the high wear resistance and rust prevention performance were improved, and the service life of the porous sieve filter was extended.

CN121380822APending Publication Date: 2026-01-23ZRIME GEARING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511813697.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-04
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing porous sieve filters have short service life in high flow rate, high particle load and corrosive media environments. Material selection and surface strengthening technology have challenges in temperature uniformity control. Secondary nitriding reduces hardness and lacks effective integration of rust prevention treatment, making it difficult to meet demanding industrial requirements.

Method used

Using 38CrMoAl steel as raw material, and combining pre-oxidation treatment, ion nitriding and post-oxidation treatment into an integrated process, temperature uniformity is controlled through auxiliary tooling design, forming a deep nitriding layer and generating a dense Fe3O4 film, thereby improving hardness and rust prevention performance.

Benefits of technology

Significantly improves the service life and operational reliability of porous sieve filters, meets the requirements for high wear resistance and rust prevention, extends the equipment service life, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121380822A_ABST
    Figure CN121380822A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of porous sieve-shaped filter manufacturing, and particularly discloses a porous sieve-shaped filter surface layer composite strengthening heat treatment method. High-quality nitriding steel 38CrMoAl serves as a raw material, machining is conducted after thermal refining, the size of a workpiece is stabilized through high-temperature stress relief annealing treatment, plasma glow nitriding treatment is conducted after machining is conducted, the uniform deep nitriding effect of a porous sieve-shaped filter is achieved through an auxiliary tool, then post-oxidation treatment is conducted, a compact Fe3O4 film is formed on the surface of the workpiece, and the high-quality nitriding steel 38CrMoAl is obtained. Contact between a corrosive medium and matrix metal is effectively isolated, and the rust-proof and corrosion-resistant capacity of a workpiece is improved. For workpieces such as a porous sieve-shaped filter requiring high wear resistance and good anti-rust performance, the combination of ion nitriding and post-oxidation treatment can realize gentle hardness gradient decreasing amplitude and surface corrosion resistance and rust prevention. The nitriding layer provides high hardness and wear resistance, the surface oxidation film endows an anti-rust function, and the nitriding layer and the surface oxidation film cooperate to achieve the composite strengthening effect of high hardness and corrosion resistance of the surface layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of porous sieve filter manufacturing technology, specifically relating to a composite strengthening heat treatment method for the surface of a porous sieve filter, and a porous sieve filter prepared using this method. Background Technology

[0002] Porous sieve filters (such as) Figure 1 (As shown) This type of filter is an industrial component widely used in solid-liquid separation and filtration purification processes. Its core function is to separate particles of different sizes through a mechanical sieving mechanism using a mesh. Structurally, this type of filter typically adopts a cylindrical design with a concave middle section. The concave section has a large number of uniformly distributed micropores along the circumference. These micropores form filtration channels of a specific diameter; the standard mesh diameter is generally 2mm, but the mesh size can be adjusted according to different workpiece specifications and application requirements. The working principle of this type of filter is based on the mechanical sieving effect of particle diameter and mesh size. When fluid passes through the filter, particles larger than the mesh size are trapped inside or on the surface of the filter, thus achieving separation. Because the working environment often involves high flow rates, high particle loads, and corrosive media, the filter components must maintain high hardness, high wear resistance, and excellent rust resistance. This type of filter is commonly found in heavy industrial fields such as petrochemicals, mining screening, and water treatment, where the working conditions are harsh and there are high requirements for the service life and performance stability of the components.

[0003] Currently, porous sieve filters are mostly manufactured using ordinary carbon steel or medium carbon steel. The processing typically involves first undergoing quenching and tempering (quenching + high-temperature tempering) to obtain a certain strength and toughness, followed by machining to form complex structures, especially the sieve holes. This material selection is primarily based on processing performance considerations—because sieve filters have a large number of densely distributed small holes, drilling and stamping processes are required during processing, and lower matrix hardness helps improve processing efficiency and reduce tool wear. However, this material selection approach has significant drawbacks. Even after quenching and tempering, the surface hardness, wear resistance, and corrosion resistance of ordinary carbon steel or medium carbon steel are still insufficient to meet the requirements of harsh working environments. This results in filters exhibiting rapid wear, short lifespan, and the need for frequent parts replacement during actual use, leading to long equipment downtime, reduced production efficiency, and increased maintenance costs. When the workpiece is worn out, it usually needs to be replaced entirely rather than repaired and reused, further increasing operating costs.

[0004] In view of the current situation, the present application attempts to use nitriding steel such as 38CrMoAl instead of ordinary carbon steel, and improves the hardness and wear resistance by surface nitriding treatment. 38CrMoAl steel is a high-quality special steel for nitriding, containing alloying elements such as aluminum, chromium and molybdenum, and can form stable and high-hardness nitrides, which is theoretically very suitable for filter workpieces requiring high wear resistance and fatigue resistance. However, in practical application, this material and processing technology combination faces multiple challenges. First, ion nitriding (also known as glow nitriding) as an advanced surface strengthening technology has achieved good results on various mechanical parts. This technology uses the principle of glow discharge, uses the workpiece as the cathode and the container wall as the anode in a vacuum container, and introduces nitrogen-containing gas (such as nitrogen, ammonia, etc.) into the container. Under the action of the electric field, the gas ionizes to form a plasma, and the positive ions of nitrogen and hydrogen bombard the workpiece surface under the acceleration of the electric field, causing the workpiece to heat and form a nitriding layer on the surface. Although ion nitriding technology has the advantages of fast penetration speed, small deformation and low energy consumption, it faces special technical difficulties when processing porous screen-shaped filters with dense small holes: (1) Difficulty in controlling temperature uniformity: During ion nitriding, the temperature of the workpiece depends on the conversion of kinetic energy to heat energy by ion bombardment. For filter workpieces with dense small holes, due to the "hollow cathode effect", the glow discharge in the small holes will be abnormally concentrated, causing the temperature of the hole wall to be significantly higher than that of other parts of the workpiece. This temperature non-uniformity causes differences in the microstructure and properties of the nitriding layer in different parts of the workpiece, and the small hole area often has problems such as increased brittle phase, uneven nitriding layer thickness, etc., affecting the overall performance and service life of the filter. (2) Hardness decrease after secondary nitriding: After being used for a period of time, the surface nitriding layer of the porous screen-shaped filter will fail due to wear and tear, and needs to be treated by secondary nitriding to restore its performance. However, it has been found in practical application that the surface hardness of the workpiece after being disassembled and re-nitriding is much lower than that after the first nitriding. This phenomenon may be related to the changes in surface microstructure, nitrogen concentration distribution characteristics and nitride conversion rules during the secondary heating process, but the specific mechanism is not clear and there is a lack of effective process control means. (3) Strict pretreatment requirements: 38CrMoAl steel needs to be appropriately quenched before nitriding (the pre-quenching temperature needs to be controlled at 900-920℃) to obtain the required matrix performance and release processing stress. However, this material is more prone to oxidation and decarburization during heat treatment, and if the machining allowance is not sufficient and the decarburized layer is not completely removed, it will cause defects such as peeling and blistering on the surface during subsequent nitriding, which seriously affects the quality of nitriding. For complex porous filters, it is also difficult to ensure that the machining allowance on the surface of each small hole is uniform.

[0005] In summary, the manufacturing and processing of the existing porous screen-shaped filter mainly has the following deficiencies: the ordinary carbon steel with good processing performance but insufficient wear resistance and corrosion resistance is mainly selected; in the surface strengthening technology, the ion nitriding has difficulty in controlling the temperature uniformity in the processing of the porous structure; in the rust prevention treatment, there is a lack of post-processing scheme effectively integrated with the nitriding process; and the performance recovery after the secondary nitriding is not ideal. Especially for the 38CrMoAl steel porous screen-shaped filter, there is no systematic research method of organic combination of ion nitriding and post-processing, and there is a lack of special solution for controlling the temperature uniformity of the porous structure. SUMMARY

[0006] The technical problem solved by the present application is to provide an integrated process method of ion nitriding and post-oxidation treatment for a porous screen-shaped filter, to solve the problem of temperature uniformity by innovative auxiliary tool design, to realize the synergistic effect of deep nitriding and surface rust prevention by optimized process parameters, and to significantly improve the service life and working reliability of such workpieces, thereby meeting the increasingly stringent industrial application requirements.

[0007] Meanwhile, the present application provides a porous screen-shaped filter prepared by the method.

[0008] To solve the above technical problems, the present application provides the following technical solutions: A surface layer composite strengthening heat treatment method of a porous screen-shaped filter, using medium carbon alloy steel 38CrMoAl as raw material, the filter workpiece is first subjected to pre-oxidation treatment, and then subjected to ion nitriding treatment and post-oxidation treatment in sequence.

[0009] As a preferred embodiment of the present application, an auxiliary tool is arranged on the periphery of the workpiece during ion nitriding, and through holes (or micropores) that are easy to heat are arranged on the auxiliary tool corresponding to the non-screen hole part (the middle section of the filter). The design idea of the auxiliary tool is as follows: ion nitriding relies on the ratio of surface area to weight to comprehensively evaluate the heating rate, when the surface area is larger and the weight is smaller, the workpiece can receive more ion nitriding bombardment, the kinetic energy is converted into heat energy, and the temperature of the workpiece is easier to rise. For the porous screen-shaped filter workpiece, the temperature of the screen hole part is easier to rise, so the auxiliary tool is added to make the temperature of other parts (non-screen hole part) of the workpiece also easy to rise.

[0010] Specifically, the auxiliary tool adopts a cylindrical design, the middle section is hollow, and a large number of through holes are distributed in the circumferential direction on the cylinder wall of the upper and lower sections. The size of the through hole is determined according to the size of the screen hole on the filter workpiece.

[0011] As a preferred embodiment of the present application, the process parameters of the pre-oxidation treatment are: air atmosphere, temperature 250-300℃, holding time 1-3 h. The purposes of the pre-oxidation treatment are mainly two aspects: the first is to evaporate the residual moisture on the surface of the workpiece in time to avoid corrosion of the workpiece to produce rust; the second is to generate a thin micron-level oxide layer (thickness <1 μm), and in the subsequent ion nitriding process, a medium mainly containing ammonia gas (NH3) is introduced, and the ammonia gas and the hydrogen gas decomposed therefrom have a certain oxidation-reduction capacity, which can cause the surface oxide to react and cause lattice distortion, and the crystal defects provide a fast channel for the subsequent nitriding, effectively improving the nitriding rate.

[0012] As a preferred embodiment of the present application, the process parameters of the ion nitriding treatment are: ammonia gas atmosphere, nitriding temperature 540-560℃, voltage 700-750 V, current 40-50 A, ammonia gas flow rate 1.0-1.2 mL / min, holding time 80-90 h. After the holding time ends, the temperature is reduced to below 300℃, the ammonia gas is stopped, the voltage and current are turned off, and the furnace is cooled to below 160℃, and the furnace is discharged and air-cooled.

[0013] As a preferred embodiment of the present application, the process parameters of the post-oxidation treatment are: nitrogen gas atmosphere, temperature 350-450℃, holding time 1-3 h; heating to 520-540℃, introducing water, holding time 1.5-2 h, and then furnace cooling. After the holding time ends, the furnace is slowly cooled to reduce the thermal stress generated by the porous sieve-shaped filter during the cooling process, and when the furnace is cooled to 150-180℃, the filter workpiece is immersed in a rapid quenching oil, the oil temperature is 40-80℃, and the workpiece is taken out of the oil and air-cooled when the workpiece temperature is consistent with the oil temperature.

[0014] As a preferred embodiment of the present application, the processing process of the porous sieve-shaped filter is: forging → high-temperature normalizing + quenching and tempering treatment → semi-finishing turning → stabilization treatment → grinding neck → drilling → cleaning → pre-oxidation treatment → ion nitriding treatment → post-oxidation treatment → finishing.

[0015] Specifically, the process parameters of the high-temperature normalizing treatment are: air atmosphere, temperature 600-700℃, holding time 0.5-1.5 h; heating to 920-950℃, holding time 2-3 h; then furnace cooling to room temperature; and then high-temperature tempering treatment, holding time 4-6 h at 600-700℃, and air cooling after the holding time ends.

[0016] Specifically, the process parameters for the quenching and tempering treatment are as follows: air atmosphere, heating rate of 40-60℃ / h, heating to 600-700℃, holding for 0.5-1.5 h; continuing to heat to 880-920℃, holding for 2-3 h; then cooling with 10% PAG quenching medium, with a maximum cooling rate of 150℃ / s, removing the workpiece from the quenching medium after it cools to 100-120℃; then holding at 600-630℃ for 4-6 h, and air cooling after removal from the furnace. The hardness of the workpiece after quenching and tempering is tested by grinding and polishing with an angle grinder, with a grinding depth of at least 1.5 mm from the surface. After the surface is smooth and flat, the surface hardness is tested, and the surface hardness does not exceed 280 HBW.

[0017] Specifically, the stabilization treatment process parameters are as follows: air atmosphere, heating rate of 40-60℃ / h, heating to 560-600℃, holding at that temperature for 4-6 h; then cooling down at a rate ≤30℃ / h, removing from the furnace and air-cooling to room temperature after the furnace temperature drops below 300℃. The stabilization treatment temperature must be higher than the subsequent ion nitriding temperature to fully release the stress during processing and prevent deformation induced by residual stress release when the ion nitriding temperature is reached. The stabilization treatment temperature must also be lower than the high-temperature tempering temperature during the quenching and tempering treatment to prevent a decrease in the basic hardness of the porous sieve filter and avoid a reduction in the strength and toughness of the matrix itself.

[0018] Specifically, the cleaning process uses a cleaning solution containing metal cleaner at a temperature of 80-90℃ to ensure that surface-adhered cutting fluid, rust-preventive oil, iron filings, and other impurities are removed. Subsequently, during furnace loading, the workpiece surface is wiped again with a clean white cloth dampened with alcohol, and the pores of the workpiece are cleaned to ensure no debris remains.

[0019] A porous sieve filter prepared using the above method.

[0020] This invention relates to a porous sieve filter made from high-quality nitrided steel 38CrMoAl. To address the rust prevention requirements of the filter workpiece in corrosive environments, ion nitriding is organically combined with post-oxidation treatment. Post-oxidation treatment, after nitriding, forms a dense Fe3O4 film on the workpiece surface under specific conditions. This oxide film possesses excellent density and chemical stability, effectively isolating the corrosive medium from the base metal, thereby improving the workpiece's rust and corrosion resistance. For porous sieve filters, which require both high wear resistance and good rust prevention, the combination of ion nitriding and post-oxidation treatment offers significant technical advantages, achieving a deep nitrided layer, a gradual hardness gradient, and surface corrosion resistance. The nitrided layer provides high hardness and wear resistance, while the surface oxide film provides rust prevention. The combination of these two synergistically achieves high surface hardness and corrosion resistance, realizing a composite strengthening of the material's surface. Furthermore, this invention achieves a uniform deep nitriding effect through auxiliary tooling design.

[0021] The surface composite strengthening heat treatment method provided by this invention can achieve micro-deformation control of thin-walled long cylindrical parts. After the raw material is quenched and tempered, it is machined and then subjected to high-temperature stress-relief annealing to stabilize the workpiece dimensions. After further machining, it is subjected to glow discharge plasma nitriding treatment + post-oxidation treatment to form a wear-resistant and corrosion-resistant layer on the workpiece surface. The subsurface is a nitrided layer, thereby significantly improving the service life of porous sieve filters. Attached Figure Description

[0022] Figure 1 This is a photograph of a porous sieve filter.

[0023] Figure 2 This is a schematic diagram of the assembly structure of the porous filter workpiece and auxiliary tooling (right: sectional view).

[0024] Figure 3 Microstructure of a porous sieve filter workpiece after quenching and tempering (left: 100×, right: 500×).

[0025] Figure 4 This is the gradient curve of the nitrided layer depth of the sample.

[0026] Figure 5 Microscopic images of the nitrided surface of the sample (left: 100×, right: 500×).

[0027] Figure 6 This is a schematic diagram of the microstructure of a porous sieve filter.

[0028] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings obtained in the experimental examples have been briefly described above. It should be understood that the above drawings only show some experimental examples of the present invention and should not be considered as any limitation on the scope of protection of the claims. For those skilled in the art, other related drawings can be obtained based on these drawings without any creative effort. Detailed Implementation

[0029] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments and experimental examples. However, those skilled in the art should understand that the embodiments are only used to illustrate the technical solution of the present invention and should not be regarded as limiting the scope of protection of the present invention. Based on the following embodiments, all other implementation schemes obtained by those skilled in the art without creative effort, such as implementation schemes obtained by modification, variation or simple substitution, should fall within the scope of protection of the present invention.

[0030] Unless otherwise specified, the experimental methods used in the following examples and experimental cases are conventional methods; the raw materials and instruments used are all commonly used items in the field and commercially available to the public unless otherwise specified; the terms and abbreviations used have their conventional meanings in the field. The 38CrMoAl medium-carbon alloy steel was purchased from Guangdong Shaoguan Zhongji Heavy Industry Co., Ltd., and conforms to the alloy element content specifications in GB / T3077-2015 "Alloy Structural Steel". The alloy element content (mass percentage) was determined using an ARL3460 direct-reading spectrometer, as shown in Table 1.

[0031] Table 1. Chemical composition (wt.%) of 38CrMoAl medium carbon alloy steel

[0032] After testing, the alloy element content of the 38CrMoAl alloy steel in the porous sieve filter meets the requirements.

[0033] Example

[0034] This embodiment provides a method for preparing a porous sieve-shaped filter. The overall processing flow is as follows: forging → high-temperature normalizing + quenching and tempering → semi-finish turning → stabilization treatment → journal grinding → drilling → cleaning → pre-oxidation treatment → ion nitriding treatment → post-oxidation treatment → finishing. Specifically, it includes the following steps: (1) High-temperature normalizing + quenching and tempering The forgings are subjected to high-temperature normalizing treatment. The heating rate is ≤80℃ / h, and the temperature is uniformly 650℃ for 60 min. Then, the heating rate is ≤80℃ / h to 930℃ and held for 150 min (holding time: effective thickness / 45-55mm, hours). After that, the forgings are removed from the furnace and air-cooled to room temperature. After the workpieces have cooled to room temperature, they are subjected to high-temperature tempering treatment, which is 650℃ for 300 min. After the tempering is completed, they are air-cooled.

[0035] Tempering treatment: Hold at 650℃ for 60 min, then raise the temperature to 900℃ at a rate of ≤80℃ / h and hold for 150 min. Then cool with 10% PAG quenching medium at a maximum cooling rate of 150℃ / s. Remove the workpiece from the furnace after cooling to 100-120℃, and then hold at 620℃ for 300 min before air cooling.

[0036] The microstructure of the workpiece after quenching and tempering is as follows Figure 3 As shown, the microstructure after quenching and tempering is mainly composed of tempered sorbite with a small amount of ferrite. According to the relevant atlases in GB / T 13320-2007 "Metallographic Structure Rating Diagrams and Evaluation Methods for Steel Forgings", the rating is level 2, meeting the requirements for normal quenching and tempering. After machining, the workpiece shows no decarburization on the surface and no obvious free ferrite, making it suitable for nitriding treatment.

[0037] Hardness test: Use an angle grinder to grind and polish the surface to a depth of not less than 1.5mm. After the surface is flat and smooth, use a TIME 5310 portable Leeb hardness tester to test the surface hardness. The surface hardness shall not exceed 280 HBS.

[0038] (2) Stabilization treatment The workpiece undergoes a stabilization treatment. First, it is held at 580℃ for 300 min (the holding time is the same as the high-temperature tempering time). Then, it is cooled at a rate ≤30℃ / h until the furnace temperature drops below 300℃, at which point it is removed from the furnace and air-cooled to room temperature. The stabilization treatment temperature must be higher than the subsequent ion nitriding temperature to fully release the stress from the processing and prevent deformation induced by residual stress release when the ion nitriding temperature is reached. The stabilization treatment temperature must also be lower than the high-temperature tempering temperature during the quenching and tempering process to prevent a decrease in the basic hardness of the porous sieve filter and to avoid a reduction in the strength and toughness of the matrix itself.

[0039] (3) Cleaning treatment To ensure the appearance quality of the workpiece after grinding the journal and drilling, a cleaning solution containing metal cleaner is first used during cleaning. The cleaning solution temperature is 80-90℃ to ensure that the cutting fluid, rust-preventive oil, iron filings, and other impurities adhering to the surface are removed. Subsequently, when loading the workpiece into the furnace, the surface is wiped again with a clean white cloth dampened with alcohol. The pores of the workpiece must be thoroughly cleaned to ensure that no debris remains.

[0040] (4) Pre-oxidation treatment After the porous sieve filter workpiece is cleaned, it is heated in an electric resistance furnace without a protective atmosphere, slowly raised to about 280℃, held at that temperature for 2 hours, and then air-cooled. The purpose of pre-oxidation is mainly twofold: first, to allow residual moisture on the surface of the workpiece to evaporate in time, so as to avoid corrosion and rust formation; second, to generate a thin micron-level oxide layer (thickness <1μm). Subsequently, during the ion nitriding process, a medium mainly composed of ammonia (NH3) is introduced, and the hydrogen gas decomposed from it has a certain redox reaction, which can effectively increase the nitriding rate.

[0041] (5) Charging the furnace before ion nitriding Ion nitriding heating relies on ion bombardment for heating. Each workpiece is a heat source, and heating is limited by the surface area / weight ratio. Combining the characteristics of bell-type ion nitriding furnace, where the upper part has a lower temperature and the lower part has a higher temperature in the middle and the inner layer has a lower temperature, each workpiece is evenly distributed and placed upright on the cathode plate. The distance between each workpiece is not less than the diameter of the workpiece itself. Then, each workpiece is supported by a cylindrical pad with a diameter of 25 mm and a height of 50 mm to ensure that the cathode plate does not affect the outer circle and bottom of the porous sieve filter. Figure 2The diagram shows the assembly structure of a cylindrical filter workpiece and auxiliary tooling. The middle section of the filter workpiece has numerous sieve holes evenly distributed along its circumference. During nitriding, the hollow cathode effect causes an increase in current density at this location, leading to localized overheating. Therefore, a cylindrical auxiliary tooling is placed around the filter workpiece. The middle section of the auxiliary tooling is hollowed out, corresponding to the sieve holes of the filter workpiece. The hollowed-out support is provided by welding small cylindrical strips. The upper and lower sections of the auxiliary tooling have numerous through holes evenly distributed along their circumference, corresponding to the non-sieve hole areas of the workpiece. In other words, the tooling cover surrounding the workpiece functions as an auxiliary cathode heating cover. It has a large surface area and thin wall thickness, allowing for easy heating during ion nitriding and thus playing a temperature control role, ensuring temperature uniformity across the workpiece during heating and cooling.

[0042] (6) Ion nitriding treatment Glow discharge ion nitriding is a surface modification technique that, compared to other nitriding methods, features rapid nitriding rate, low brittleness, controllable phase composition, and minimal deformation. It utilizes the glow discharge phenomenon to bombard the surface of a part with nitrogen ions generated from the ionization of nitrogen-containing gas, thereby heating and nitriding to obtain a nitrided surface layer—an ion chemical heat treatment process. Specifically, after placing the workpiece in the furnace, turn on two vacuum pumps to evacuate the internal pressure of the furnace hood to below 60 Pa. Then, rotate the voltage to 650 V and the current to 15 A, and gradually increase the duty cycle value to allow the workpiece inside the furnace to begin arcing, eliminating surface impurities and gradually increasing the temperature. After the workpiece reaches 200℃, maintain the temperature for 2 hours. Then, when the workpiece reaches about 260℃, introduce ammonia gas heated in a 600℃ ammonia decomposition furnace into the furnace at a flow rate of 0.3 mL / min. Turn off one vacuum pump. After the workpiece reaches 400℃, maintain the temperature for 2 hours, ensuring the heating rate does not exceed 30℃ / h. When the temperature reaches the nitriding temperature (540-560℃), increase the voltage to 700 V, adjust the current to 40 A, maintain the ammonia flow rate at 1.0 mL / min, and control the holding time to 85 minutes. h, after the heat preservation is completed, reduce the temperature to below 300℃, stop the ammonia gas supply, turn off the voltage and current, cool the furnace to below 160℃, and then air cool the furnace.

[0043] Ion nitriding test: The surface hardness of ion nitrided surfaces is tested according to GB / T 34883-2017 "Ion Nitriding" standard. The surface hardness of the sample is tested using the Vickers hardness method, and the testing force is 5.0 kgf. The rectangular strip sample size is 15×15×40 mm. To ensure that the sample results are as representative as possible of the local state of the nearby workpiece, one sample is placed in the auxiliary tooling cover, one in the workpiece sieve hole, and one in the lower solid part. The sample in the sieve hole is defined as sample 1. Small holes with a 3×3 matrix and a hole diameter of 2 mm are punched on the side of sample 1 (the sample shape is similar to that of the middle hole part). The sample in the lower solid part is defined as sample 2. The two samples are placed as close as possible to the workpiece surface, but still need to maintain a gap of about 15 mm (a certain distance from the workpiece, but not enough to affect the workpiece) to ensure that it will not affect the temperature near the workpiece.

[0044] When testing the surface hardness of the sample, the surface needs to be ground and polished. The test of the ion nitriding layer is carried out in accordance with the inspection standard GB / T11354-2005 "Determination of Nitriding Layer Depth and Metallographic Structure of Steel Parts", which includes the inspection of the compound layer and the effective hardness layer depth of the nitriding layer. The test location is the cross-section of the sample, and the effective depth of the nitriding layer is determined by the hardness method.

[0045] The gradient curve of the nitrided layer depth of the sample is as follows: Figure 4 As shown in the figure, the hardness gradient curves reveal a gentle decrease in hardness. Using a core hardness of +50 HV as the boundary, the boundary hardness value is 375.3 HV. The effective nitrided layer depths of the two samples are 0.652 mm and 0.661 mm, respectively, with a small difference. Considering testing errors, the effective nitrided layer depths of both samples are considered to be similar. The Vickers hardness values ​​of the sample surfaces are shown in Table 2. Both samples have a surface hardness value ≥1000 HV5, indicating brittleness level 1 and porosity level 1.

[0046] Table 2 Micro Vickers hardness values ​​of sample surfaces

[0047] The microstructure of the nitrided surface layer, such as Figure 5 As shown, sample 2, from the surface inwards, consists of a compound layer (commonly known as the bright white layer), a diffusion layer, and a substrate. The bright white layer is approximately 8 μm thick and contains vein-like nitrides parallel to the surface, rated at level 3, which meets the technical requirements. The high grade of the vein-like nitride structure is mainly due to the fact that during the deep penetration nitriding process, the precipitation rate of nitrides at the grain boundaries is lower than the propagation rate of the precipitable zone, resulting in the accumulation of vein-like nitrides in the subsurface layer.

[0048] (7) Post-oxidation treatment The post-oxidation treatment utilizes an intelligent pit-type resistance furnace. First, the surface of the workpiece after ion nitriding is thoroughly cleaned and wiped with a white scouring pad, ensuring no oil residue remains. Then, the workpiece is loaded into the furnace using a rack fixture. The effective dimensions of the furnace chamber are 1500 × 2500 mm in diameter. Specific procedures include: first, loading the furnace at room temperature; then, heating to 180°C and introducing nitrogen gas; and holding at 180°C for 2 hours, with the nitrogen flow rate not less than 15.0 m³ / h. 3 The key point is that the nitrogen flow rate must not be less than three times the furnace volume to ensure that any residual oxygen in the pit-type resistance furnace is completely removed. Then, the temperature is slowly increased at a rate not exceeding 60℃ / h, and then raised to 400℃. During the heating process, the nitrogen flow rate can be appropriately reduced to ensure the furnace pressure is maintained at 1.5±0.2 kPa. After holding at 400℃ for 2 hours, the temperature is increased to 520℃. Water is then introduced into the furnace using a metering pump. Based on the characteristic of water directly vaporizing at high temperatures, and with the agitation of the fan above the furnace cover, the atmosphere inside the furnace is homogenized. After the holding period, slow cooling is used to reduce the thermal stress on the porous sieve filter. When the furnace cools to 150-180℃, the rack holding the workpiece is lifted out as a whole and then immersed in oil at 50℃. When the workpiece reaches the same temperature as the oil, it is removed from the oil and air-cooled. Finally, the surface of the workpiece is wiped clean with a clean white cloth.

[0049] The post-oxidation treatment uses a pit furnace with nitrogen and water vapor as the permeation medium. First, nitrogen is used to purge the air from the furnace. Then, a certain amount of water is introduced at high temperature, causing the water to vaporize and form an oxide film mainly composed of Fe3O4 with the iron. After the workpiece cools down, it is immersed in an oil bath for sealing treatment, which makes the surface of the workpiece appear black and shiny.

[0050] This embodiment also provides a porous sieve-shaped filter prepared by the above method, and a schematic diagram of its microstructure from the surface inward is shown below. Figure 6 As shown.

[0051] In other embodiments of the present invention, the process parameters in the preparation method of the porous sieve filter and the surface composite strengthening heat treatment method can be arbitrarily selected within a given range, which basically does not affect the microstructure and performance of the porous sieve filter.

[0052] Although the technical solution of the present invention has been described in detail above with general descriptions, specific embodiments, and experimental examples, it should be noted that the embodiments and experimental examples are only used to illustrate the technical solution and technical effects of the present invention, and should not be regarded as any limitation on the scope of protection of the present invention. Simple modifications, alterations, or improvements made based on the technical concept of the present invention are all within the scope of protection claimed by the present invention.

Claims

1. A method for composite strengthening heat treatment of the surface layer of a porous sieve-shaped filter, characterized in that: Using medium carbon alloy steel 38CrMoAl as raw material, the filter workpiece undergoes pre-oxidation treatment after forming, followed by ion nitriding treatment and post-oxidation treatment.

2. The heat treatment method according to claim 1, characterized in that: During the ion nitriding process, an auxiliary tool is placed around the filter workpiece, and through holes are provided on the auxiliary tool corresponding to the non-sieve hole parts of the filter workpiece.

3. The heat treatment method according to claim 1, characterized in that: The process parameters for the pre-oxidation treatment are: air atmosphere, temperature 250-300℃, and heat preservation for 1-3 hours.

4. The heat treatment method according to claim 1, characterized in that: The process parameters for the ion nitriding treatment are: ammonia atmosphere, nitriding temperature 540-560℃, voltage 700-750 V, current 40-50 A, ammonia flow rate 1.0-1.2 mL / min, and heat preservation for 80-90 h.

5. The heat treatment method according to claim 1, characterized in that: The process parameters for the post-oxidation treatment are: nitrogen atmosphere, temperature 350-450℃, holding for 1-3 hours; heating to 520-540℃, introducing water, holding for 1.5-2 hours, and then cooling down in the furnace.

6. The heat treatment method according to claim 1, characterized in that: The processing flow of the porous sieve filter is as follows: forging → high temperature normalizing + quenching and tempering treatment → semi-finish turning → stabilization treatment → journal grinding → drilling → cleaning → pre-oxidation treatment → ion nitriding treatment → post-oxidation treatment → finishing.

7. The heat treatment method according to claim 6, characterized in that: The process parameters for the high-temperature normalizing treatment are as follows: air atmosphere, temperature 600-700℃, holding for 0.5-1.5 h; heating to 920-950℃, holding for 2-3 h; then air cooling to room temperature; followed by high-temperature tempering treatment, holding at 600-700℃ for 4-6 h, and air cooling after the holding period. And / or, the process parameters for the quenching and tempering treatment are as follows: air atmosphere, heating rate of 40-60℃ / h, heating to 600-700℃, holding for 0.5-1.5 h; continuing to heat to 880-920℃, holding for 2-3 h; then cooling with 10% PAG quenching medium, the maximum cooling rate of the quenching medium is 150℃ / s, the workpiece is cooled to 100-120℃ and then removed from the liquid; then held at 600-630℃ for 4-6 h, and then air-cooled after removal from the furnace.

8. The heat treatment method according to claim 6, characterized in that: The process parameters for the stabilization treatment are as follows: air atmosphere, heating rate of 40-60℃ / h, heating to 560-600℃, holding for 4-6 h; then cooling down at a rate of ≤30℃ / h, and after the furnace temperature is below 300℃, the furnace is removed and air-cooled to room temperature.

9. The heat treatment method according to claim 6, characterized in that: The cleaning process uses a cleaning solution containing metal cleaning agents, with the cleaning solution temperature at 80-90℃.

10. A porous sieve filter prepared by the heat treatment method as described in any one of claims 1-9.